Pengaruh Persepsi Atas Sarana Prasarana Pembelajaran dan Perhatian Orang Tua terhadap Prestasi Belajar IPS - Arie Irfan Nuri; Sumaryoto Sumaryoto (Herodotus: Jurnal Pendidikan IPS, 2023)
The purpose of this study was to find out 1). The influence of perceptions of learning infrastructure and parental attention together on social studies learning achievement of private junior high school students in Bekasi, 2). The effect of perceptions of learning infrastructure on social studies learning achievement of private junior high school students in Bekasi, 3). The effect of perceptions of parents' attention on social studies learning achievement of private junior high school students in Bekasi. The sample used was 60 students as the research sample using proportional random sampling technique with multiple linear regression test. Based on the results of the hypothesis and data analysis, it is concluded as follows: 1) There is a significant influence on the perception of learning infrastructure and parental attention together on the social studies learning achievement of private junior high school students in Bekasi. This is evidenced by the value of Sig = 0.009 <0.05 and Fcount = 5.067, 2). There is a significant influence on the perception of learning infrastructure on the social studies learning achievement of private junior high school students in Bekasi. This is evidenced by the value of Sig = 0.042 <0.05 and t = 2.080, 3). There is a significant effect of parental attention on social studies learning achievement of junior high school students in Bekasi. This is evidenced by the value of Sig = 0.024 <0.05 and tcount = 2.317.